Opening the gateway to oral participation: exploring facilitative contextual factors in the association between student shyness and hand raising - Mundelsee, Lukas; Jurkowski, Susanne (American educational research journal, 2025)
This field study examined factors that might influence hand raising in students with high levels of shyness. Data were assessed using student self-reports of shyness and social relatedness factors (student-teacher relationship and peer relationship), observations of instructional factors (wait time, warm calling, class size, and school subject), and behavioral measures of hand raising among 204 middle school students during a school week. Multilevel analyses show that student-teacher relationship and warm calling facilitate hand raising of highly shy students, but also that they less likely raise their hands the better their peer relationship. Thus, the results suggest that both social relatedness and instructional factors can promote hand raising in highly shy students, opening the gateway to their oral participation.